Performance of the DSSAT MANIHOT-Cassava model for cassava cultivation in the Reconcavo Baiano /Performance do modelo DSSAT MANIHOT-Cassava para cultivo de mandioca no Reconcavo Baiano - deMelo, Diego M; de Bongiovani, Paola F; Costa, Fabio L.S; Moreno-Cadena, Patricia; Heinemann, Alexandre B; Ramirez-Villegas, Julian; Filho, Mauricio A. Coelho (Revista brasileira de engenharia agrícola e ambiental, 2025)
The aim of the present study was to calibrate the DSSAT MANIHOT-Cassava model with information from cassava varieties grown in the Reconcavo Baiano region, Bahia state, Brazil. The database used to calibrate the model was obtained in the dry sub-humid tropical climate in Cruz das Almas city, from 2019 to 2020. The model was calibrated with experimental data obtained under irrigated and rainfed conditions for the BRS Novo Horizonte and Eucalipto varieties. The calibration was carried out by adjusting parameters related to the characteristics of each variety. Model performance was evaluated with statistical indices that indicate the precision and accuracy of the simulations, such as the root mean square error and coefficients of determination, the Willmott index, and the performance index. The model, regardless of the variety, adequately simulated most of the variables studied during the calibration and validation stage, with reliability considered excellent or optimal and minor errors than the default variety for most of the variables simulated. An exception was simulation of the leaf area index, which did not properly represent the leaf senescence or regrowth phase 180 days after planting, showing overestimations for the BRS Novo Horizonte variety and underestimations for the Eucalipto variety. The model can be applied for reliably simulating performance of the cassava varieties under the sub-humid conditions of the Reconcavo Baiano. Key words: Manihot esculenta Crantz, crop simulation models, biometrics, parametrization O objetivo do presente estudo foi calibrar o modelo MANIHOT-Cassava com informac.6es de variedades de mandioca cultivadas na regiao do Reconcavo Baiano, Bahia, Brasil. A base de dados utilizada para calibracao do modelo foi obtida no clima tropical subumido seco de Cruz das Almas, no periodo de 2019 a 2020. O modelo foi calibrado com dados experimentais obtidos em condic.6es irrigadas e de sequeiro para as variedades BRS Novo Horizonte e Eucalipto. A calibracao foi realizada ajustando parametros relacionados as caracteristicas de cada genotipo. O desempenho do modelo foi avaliado a partir de indices estatisticos que indicam a precisao e acuracia das simulates, como a raiz do erro quadratico medio e coeficientes de determinac.ao, o indice de Willmott e o indice de desempenho. O modelo, independente da variedade, simulou adequadamente a maioria das variaveis estudadas durante a etapa de calibracao e validacao, com confiabilidade considerada excelente ou otima e menores erros que a variedade default para a maioria das variaveis. A excecao foi a simulac.ao do indice de area foliar, que nao representou adequadamente a fase de senescencia ou rebrota foliar 180 dias apos o plantio, apresentando superestimacoes para a variedade BRS Novo Horizonte e subestimac.6es para a variedade Eucalipto. O modelo pode ser utilizado para simular de forma confiavel o desempenho das variedades de mandioca nas condic.6es subumidas do Reconcavo Baiano. Palavras-chave: Manihot esculenta Crantz, modelos de simulac.ao de cultivos, biometria, parametrizac.ao